2023
DOI: 10.1039/d3ee03121g
|View full text |Cite
|
Sign up to set email alerts
|

A review of progress in proton ceramic electrochemical cells: material and structural design, coupled with value-added chemical production

Yakun Wang,
Yeqing Ling,
Bin Wang
et al.

Abstract: Improved performance of proton ceramic electrochemical cells (PCECs) through material development and structural design, and application of PCECs for efficient energy conversion render them promising for clean energy and sustainable development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(12 citation statements)
references
References 419 publications
0
12
0
Order By: Relevance
“…Besides water-induced exsolution, other methods have been proposed to generate NPs on surface including treating Ba 0.95 Ag 0.5 Co 0.8 Nb 0.1 Ta 0.1 O 3−δ under a reductive atmosphere and voltage-driven exsolution in Ln 0.2 Ba 0.8 Co 0.7 Fe 0.3 O 3−δ . , These works demonstrated that in situ formation of NPs on the surface is an exceptional method to enhance the catalytic activity of an air electrode. However, in previous works, in situ formation of NPs requires a reductive atmosphere or the introduction of vapor for a long time, which is not convenient enough for practical operation. Hence, there is an imminent need to advance a more facile in situ exsolution approach, for example, thermal-induced exsolution, which has attracted increasing attention recently, and the few works focused on it proved its wide potential in the PCC field. , …”
Section: Introductionmentioning
confidence: 99%
“…Besides water-induced exsolution, other methods have been proposed to generate NPs on surface including treating Ba 0.95 Ag 0.5 Co 0.8 Nb 0.1 Ta 0.1 O 3−δ under a reductive atmosphere and voltage-driven exsolution in Ln 0.2 Ba 0.8 Co 0.7 Fe 0.3 O 3−δ . , These works demonstrated that in situ formation of NPs on the surface is an exceptional method to enhance the catalytic activity of an air electrode. However, in previous works, in situ formation of NPs requires a reductive atmosphere or the introduction of vapor for a long time, which is not convenient enough for practical operation. Hence, there is an imminent need to advance a more facile in situ exsolution approach, for example, thermal-induced exsolution, which has attracted increasing attention recently, and the few works focused on it proved its wide potential in the PCC field. , …”
Section: Introductionmentioning
confidence: 99%
“…Solid oxide fuel cells (SOFCs) offer a promising technology for generating clean electricity, which is of paramount importance in the pursuit of carbon neutrality. In contrast to conventional oxygen ion-conducting SOFCs, protonic ceramic fuel cells (PCFCs) show great potential due to their ability to operate within intermediate temperature ranges (500–700 °C), facilitated by lower activation energy for proton transport. Steam is generated on the cathode side, preventing fuel dilution on the anode and ensuring resilience against oxidation in the commonly used Ni-based cermet anode . However, the sluggish reaction kinetics of cathode materials at these intermediate temperatures significantly limit PCFC performance. , Therefore, an urgent need arises for the development of cathode materials with high activity and stability to drive the commercialization of PCFCs.…”
Section: Introductionmentioning
confidence: 99%
“…Protonic ceramic electrochemical cells have been increasingly considered as a promising technology to achieve the carbon-neutral energy cycle via direct conversion of renewable power into hydrogen. 1–4 In the fuel cell mode, the chemical energy in stored hydrogen is effectively transformed into a new form of power, with water being the only byproduct. This process avoids carbon emissions.…”
Section: Introductionmentioning
confidence: 99%